The Effects of Containment Measures as Counter Banditry Activities on Igabi Local Government Area of Kaduna State - Sale, Aminu Abdullahi; Abubakar, Anas (Kashere Journal of Politics and International Relations, 2025)
Banditry is a serious security threat that has distorted the security architecture of Igabi Local Government Area of Kaduna State, it caused the loss of lives and properties. Many measures taken to tackle banditry activities proved abortive, leading to the introduction of Containment Measures as an alternative approach. This paper is, therefore, aimed at assessing the Effects Containment Measures have in counter banditry activities as well as the effects caused to the people of Igabi L.G.A. The study used quantitative method of gathering data where total of 100 questionnaires were administered, out of which 89 were retrieved. The research also used secondary source of data gathering such as textbooks, journals, online publications etc. and random sampling method was carried out in administering the questionnaires. The data gathered was analyzed into simple frequency distribution tables. The paper employed Frustration Aggression Theory as its theoretical framework. The findings of the paper revealed that containment measures have played an important role in counter-banditry activities in Igabi L.G.A, because many bandits were neutralized and weapons were intercepted. However, the measures have caused significant levels of socio-economic hardships to the people of Igabi L.G.A. The research recommended that, banditry can be mitigated by providing superior technologies among others while the effects of Containment Measures caused to the people of Igabi L.G.A. can be minimized through provision of alterative employment, grant and softloan and alternative public transport vehicles etc.